Possibilities for interactive teaching with the Jamboard virtual whiteboard (Research, Society and Development, 2022)
The present work deals with the contribution of a course on Google's interactive virtual board - Jamboard - applied to teaching teachers at the beginning of the Covid 19 pandemic, in the year 2020. Jamboard is characterized as a technological resource aimed at the area and the scope of this work was to evaluate its potential as an aid in the teaching and learning process of students, as well as the course's contribution to the development of classes in the remote modality. This board allows the teacher to write, demonstrate equations, correct activities, apply assignments, among other activities. It can be used via Google Drive, but it can also be opened during a class via Google Meet, allowing information to be shared with all class participants. At the end of the course, a questionnaire was applied and its analysis indicated that, among the 30 participants, none of them had experience in distance learning (remotely); all of them had little knowledge about the technologies available for teaching. All said they liked Jamboard a lot for its practicality and for allowing them to develop activities in a playful and interactive way. All teachers indicated that they were missing a framework for the development of their classes and indicated the need for continuing education courses to train education professionals to work with the technologies available for teaching; courses that distinguished each of these technologies according to their purpose, because despite being many, the participants did not know how to distinguish them.